Problems of seniors in House of Day’s Stay - challenge for nurse - Borowiak, Ewa; Barylska, Agnieszka (Nursing Problems / Problemy Pielęgniarstwa, 2007)
Background. Senescence of the society is very large challenge for workers of protection, especially for nurses whose task is to identify and help in problems’ solving of psychical, biological and also social sphere of the patients. The intermediate form of care over seniors, between the home care and institutional care are the Houses of Daily Care. Aim. Analyze the factors determining the quality of the seniors’ life staying in the Houses of Daily Care as well as indicating the significant role of the nurses. Material and methods. The study was carried out on 25 people above the age of 65 who systematically attended one of the Houses of Daily Care. During the direct contact the respondents were interviewed for the basic data. The assessments of: quality of life (the EuroQol5D questionnaire), state of nourishing (the MNA questionnaire), analysis of the respondents’ mood (the GDS), functioning of the basic psychical processes (the MMSE), the motor activity (the SDPAR questionnaire, Stanford questionnaire) as well as the functional efficiency (the ADL and IADL scales) were conducted. Results and conclusions. It seems that the existence of chronic cardiological illnesses, intensification of depression symptoms as well as state of nourishing determine the quality of older persons’ life staying in the Houses of Daily Care. The nurse working in the protective institution should pay special attention to nourishing state as well as older persons’ mood. The very important task of the nurses is the improvement of quality of seniors’ life by improving their nourishing state as well as their mood.